1993
DOI: 10.1088/0954-3899/19/12/017
|View full text |Cite
|
Sign up to set email alerts
|

Fission of27Al nucleus by 69 MeV monochromatic photons

Abstract: A b s b d . Monochromatic photon beams have been used to investigate lhe photofission of "AI at 69 MeV with plastic nuclear-track detectors. The measured fissility was found to he (5.7 * 1.1) X lo-'. Wis result, along with the available data for "' Sm and '74Yb nuclei taken at the same energy, has been interpreted within the frameaork of a two-step model for the photofission reaction. According to this model the incoming photon is considered to he absorbed by a neutron-proton pair, and then followed by an evap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 40 publications
5
19
0
Order By: Relevance
“…These latter data represent the unique available information in the region of intermediate-mass nuclei. As expected it is found that, within the referred uncertainties, the set of data points obtained at k = 100 MeV lies between the fissility trends calculated for monoenergetic photons of 69 MeV [25,27] (full line) and of 600 MeV [39] (dotted line). Moreover, the data appear closer to the fissility trend calculated for 69 MeV than to that for 600 MeV.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…These latter data represent the unique available information in the region of intermediate-mass nuclei. As expected it is found that, within the referred uncertainties, the set of data points obtained at k = 100 MeV lies between the fissility trends calculated for monoenergetic photons of 69 MeV [25,27] (full line) and of 600 MeV [39] (dotted line). Moreover, the data appear closer to the fissility trend calculated for 69 MeV than to that for 600 MeV.…”
Section: Discussionsupporting
confidence: 74%
“…As far as the 51 V and nat Ti targets are concerned, it is worth noticing that, for nuclei lighter than silver, both a study of nuclear fissility throughout the periodic table [38] and Monte Carlo calculations of photon-induced reactions based on the cascadeevaporation model [39] have indicated a clear trend of increasing fissility with decreasing Z 2 /A. Recently, in a study of 27 Al fission by 69 MeV monochromatic photons [27], such calculations have been extended towards less massive nuclei (left portion of the full line in figure 4). Although no trend of calculated fissility is at present available for incident photons of 100 MeV, the experimental values here determined for 51 V and nat Ti (∼ 10 −2 ) seem to confirm the predicted increasing of fissility for fissioning systems with Z 2 /A 20.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations